EGFR and KRAS mutation analysis in cytologic samples of lung adenocarcinoma enabled by laser capture microdissection - Chowdhuri, Sinchita Roy (Mod Pathol, 2011)
The discovery of activating mutations in EGFR and KRAS in a subset of lung adenocarcinomas was a major advance in our understanding of lung adenocarcinoma biology, and has led to groundbreaking studies that have demonstrated the efficacy of tyrosine kinase inhibitor therapy. Fine-needle aspirates and other cytologic procedures have become increasingly popular for obtaining diagnostic material in lung carcinomas. However, frequently the small amount of material or sparseness of tumor cells obtained from cytologic preparations limit the number of specialized studies, such as mutation analysis, that can be performed. In this study we used laser capture microdissection to isolate small numbers of tumor cells to assess for EGFR and KRAS mutations from cell block sections of 19 cytology samples from patients with known lung adenocarcinomas. We compared our results with previous molecular assays that had been performed on either surgical or cytology specimens as part of the patient’s initial clinical work-up. Not only were we able to detect the identical EGFR or KRAS mutation that was present in the patient’s prior molecular assay in every case, but we were also able to consistently detect the mutation from as few as 50 microdissected tumor cells. Furthermore, isolating a more pure population of tumor cells resulted in increased sensitivity of mutation detection as we were able to detect mutations from laser capture microdissection-enriched cases where the tumor load was low and traditional methods of whole slide scraping failed. Therefore, this method can not only significantly increase the number of lung adenocarcinoma patients that can be screened for EGFR and KRAS mutations, but can also facilitate the use of cytologic samples in the newly emerging field of molecular-based personalized therapies.